Prospective multicentre study of rectal carriage of multidrug-resistant Enterobacteriaceae among health-care workers in Spain. (May 2020) - Fernández-Verdugo, A.; Forcelledo, L.; Rodríguez-Lozano, J.; Rodríguez-Lucas, C.; Barreiro-Hurlé, L.; Canut, A.; de la Iglesia, P.; Escudero, D.; Calvo, J.; Boga, J.A.; Margolles, M.; Rodicio, M.R.; et al.
Abstract: Objectives: To investigate the rectal carriage of multidrug-resistant Enterobacteriaceae (colistin-resistant, extended-spectrum β-lactamase (ESBL) -producers and/or carbapenemase-producers) among health-care workers (HCWs) from six Spanish hospitals. Methods: Rectal swabs from 258 HCWs, employed in intensive care units, haematology wards and clinical microbiology laboratories from six hospitals in northern Spain were studied. They were cultured in selective media for Gram-negative resistant bacteria. Detection of antimicrobial resistance genes and multilocus sequence typing were performed by PCR and further sequencing. A questionnaire including data related to risk factors of colonization/infection by resistant bacteria (age, gender, chronic diseases, immunosuppressive therapies, invasive procedures or antimicrobial treatments) was given to each participant. Results: No carbapenemase-producing Enterobacteriaceae were recovered. However, 8/258 HCWs (3.1%) were positive for ESBL-producing isolates. This rate was not higher than the colonization rate previously reported in Spain for healthy people in the community. Five isolates showed high-level resistance to colistin (MICs ranging from 8 to 128 mg/L) but all of them were negative for the mcr genes tested. No statistically significant risk factors for gut colonization by ESBL-producing or colistin-resistant Enterobacteriaceae were identified among the HCWs participating in the study. Conclusions: Our data suggest that working in hospitals does not represent a risk for rectal carriage of multidrug-resistant Enterobacteriaceae.